2007
DOI: 10.1097/sla.0b013e3180caa3fb
|View full text |Cite
|
Sign up to set email alerts
|

Activities of Daily Living and Quality of Life of Elderly Patients After Elective Surgery for Gastric and Colorectal Cancers

Abstract: Objective: To establish reliable standards for surgical application to elderly patients 75 years old or older with gastric or colorectal cancer with special reference to the postoperative recovery of activities of daily living (ADL) and quality of life (QOL). Summary Background Data: ADL and QOL are important outcomes of surgery for the elderly. However, there has been only limited evidence on the natural course of recovery of functional independence. Methods: Two hundred twenty-three patients 75 years old or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
96
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 137 publications
(103 citation statements)
references
References 26 publications
(16 reference statements)
4
96
0
1
Order By: Relevance
“…The prognosis of patients with EGC after curative surgery is highly favorable with reported 5-year survival rates in the excess of 90% [3], therefore, the quality of lives of these patients has greatly been emphasized [4]. Considering the quality of life (QOF), endoscopic mucosal resection/r endoscopic submucosal dissection (EMR/ESD) is now widely accepted for mucosal gastric cancers without lymph node metastasis [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The prognosis of patients with EGC after curative surgery is highly favorable with reported 5-year survival rates in the excess of 90% [3], therefore, the quality of lives of these patients has greatly been emphasized [4]. Considering the quality of life (QOF), endoscopic mucosal resection/r endoscopic submucosal dissection (EMR/ESD) is now widely accepted for mucosal gastric cancers without lymph node metastasis [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The surgical risk predictive scales such as POSSUM and E-PASS were the associated risk factors. 3 We observed a disability rate of 17%. These differences with our results appear to derive from differences in the composition of the studied participants.…”
mentioning
confidence: 64%
“…Postoperative complications are associated with an ADL declined. 3 We found that disability was related with impairment in HRQoL. Consequently, postoperative complications, through the limitations for ADL, could explain its negative effect on HRQoL.…”
mentioning
confidence: 75%
See 2 more Smart Citations